INCREASE PRODUCTION COMPETITIVENESS OF SME’S “MADIREDO” AT KEC. PUJON KAB. MALANG THROUGH DIVERSIFICATION OF PRODUCTION AND ONLINE SHOP - Sigit Kusmaryanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2017)
SMEs Cracker Madiredo Village Pujon District Malang Regency is a business group housewife mother spread in two areas in village Madiredo Kec.pujon, Kab Malang. This business has grown and become a pilot business in the village Madiredo Pujon District Malang regency.Currently, the production capacity of SMEs has reached 50 kg / group. However, due to the simple marketing model of production, the average sales per day in each week is only about 25 kg. As a result stocks accumulate making SME production is not continuous . Production of onion crackers are sold only in the form of raw crackers. Production packaging is not well covered, unappealing and even unimpressed, which results in a decline in production resistance. While marketing is done by depositing / selling directly to market traders around Pujon and Batu.